Performance of Synthetic Pesticides against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) under Laboratory Conditions - Shah Rashdi, Syed Muzafar Ali; Gilal, Arfan Ahmed; Rajput, Lubna Bashir; Soomro, Din Muhammad; Muhammad Adeel,; Khaskheli, Farzana Zahid; Rashdi, Mudassar Ali Shah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Fall armyworm (FAW), Spodoptera frugiperda is a native insect pest of maize crop in South America. It has become an invasive species after its introduction in Sindh, Pakistan. Considering various options for its management, this study was conducted to determine the effectiveness of different pesticides (Proclaim 0.19EC, Coragen 28SC, Match 50EC and Runner 240SC) against 3rd, 4th, and 5th instar larvae of fall armyworm. The pesticides were prepared at half and full recommended doses as per the specifications of the manufacturer. The results regarding mortality percentage were recorded after 24, 48, 72, 96, 120, 144 and 168 hrs. The results indicated that the mortality percentage of FAW in all pesticides at both doses increased with time duration and reached a maximum at 168 hrs. Similarly, all pesticides mostly killed 50 to 100% larval population of FAW after 48 to 168 hrs at half and full doses. The Proclaim shows 100% mortality percentage on half and full dose against 3rd, 4th, and 5th instar larvae, followed by Coragen and Runner. Among pesticides, Match was found least effective. Among doses, maximum mortality of FAW in all pesticides was recorded at full dose as 5th instar larvae were found most susceptible, followed by 4th and 3rd instar. Therefore, it is suggested that a proper application schedule of pesticides, especially Proclaim and Coragen, should be included in the integrated management of FAW in maize to reduce its damage.